Intermetallic formation and oxidation in AL-AU system - Xu, Cong (2008)
Al-Au system has drawn a lot of research interests due to its wide use in microelectronic packaging technology for making interconnections, but the controversies over the interface intermetallic phases and some diffusional aspects have not been resolved. Further, no systematic investigations appear to have been reported on the effects of anneal temperature and time.